1999
DOI: 10.1104/pp.121.2.557
|View full text |Cite
|
Sign up to set email alerts
|

A Proline-, Threonine-, and Glycine-Rich Protein Down-Regulated by Drought Is Localized in the Cell Wall of Xylem Elements

Abstract: A cDNA clone encoding a proline-, threonine-, and glycine-rich protein (PTGRP) was isolated from a wild tomato species (Lycopersicon chilense) (L.X. Yu, H. Chamberland, J.G. Lafontain, Z. Tabaeizadeh [1996] Genome 39: 1185-1193). Northern-blot analysis and in situ hybridization studies revealed that PTGRP is downregulated by drought stress. The level of the mRNA in leaves and stems of 8-d drought-stressed plants decreased 5-to 10-fold compared with that in regularly watered plants. The mRNA reaccumulated when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 39 publications
(41 reference statements)
0
20
1
Order By: Relevance
“…The level of the mRNA in leaves and stems of 8-d drought-stressed plants decreased 5-to 10-fold compared with that in regularly watered plants. Proline-threonine-glycine-rich protein (PTGRP) was the first drought-regulated protein that has been precisely localized in the cell wall (Harrak et al, 1999). In our research, the RNA-blot analysis showed that ''GBAS23'' appeared to be upregulated at the second week of drought stress; however, at the third week a very weak hybridization signal was observed.…”
Section: Discussioncontrasting
confidence: 47%
“…The level of the mRNA in leaves and stems of 8-d drought-stressed plants decreased 5-to 10-fold compared with that in regularly watered plants. Proline-threonine-glycine-rich protein (PTGRP) was the first drought-regulated protein that has been precisely localized in the cell wall (Harrak et al, 1999). In our research, the RNA-blot analysis showed that ''GBAS23'' appeared to be upregulated at the second week of drought stress; however, at the third week a very weak hybridization signal was observed.…”
Section: Discussioncontrasting
confidence: 47%
“…Nonsynonymous mutations arising de novo in this domain of the subfamilies after the duplication conferred new functional features to the gene apparently had adaptive significance and thus became maintained in the population. For instance, replacing polar amino acid serine by nonpolar proline in ATP͞GTP binding site of kaiIIId1 likely is adaptive to desiccation, because proline was shown to be related to drought-stress response (52)(53)(54). The substitutions in the 51-61 amino acid region probably have similar adaptive significance, because they are generally in favor of hydrophobic amino acids.…”
Section: Driving Forces Of Kai Gene Family Evolution: Selection Vs Nmentioning
confidence: 99%
“…For the native primary cell wall, it is known that lignin can make covalent cross-links with both protein and pectin (Harrak et al 1999). It is also suggested that xyloglucan is hydrogen bound to cellulose and covalently bound to pectin (Bacic et al 1988;Whitney and Gidley 1999).…”
Section: Introductionmentioning
confidence: 98%